Buyer-supplier relationships in Malaysian pineapple industry supply chain - Rajendran, Salini Devi (2013)
Pineapple or locally called as nanas is the second important tropical fruit after bananas which contributes over 20% of the world production of tropical fruits. The Malaysian pineapple industry is dominated by both estate holders and small scale farmers. The pineapple industry has a high potential to develop as it contributes high positive return to the country’s economy. Realizing the importance of this industry, the government has formed a statutory body, the Malaysian Pineapple Industrial Board (MPIB) to provide attention to all matters related to the pineapple industry. Generally, the main systems being applied in the Malaysian pineapple industry are contract farming and non-contract farming. Even though contract farming is an effective way to ensure income and profit to both farmers and buyers, most of small scale farmers in the pineapple industry are preferred not to involve in contract farming and bind with any players in the industry. Both farmers and buyers need to ensure that the relationship they developed will lead to the efficiency of pineapple supply chain. In doing that, both players need to focus attention on price, quality, quantity, and delivery as well as other intangible elements such as trust, commitment, cooperation, satisfaction, power/dependence,reputation, and loyalty. In the light with the scenario in the Malaysian pineapple industry, an issue is addressed in this study on what factors influence the long-term relationships between the non-contract buyers and growers. Thus, this study investigated the long-term relationship between buyers and growers in enhancing supply chain management of the pineapple industry in Malaysia. The study was conducted in the southern region of Malaysia, the state of Johor among 171 growers and 69 buyers. The sample of the growers and buyers were chosen based on random sampling from the directories of MPIB and FAMA 2011. Face-to-face interviews with the respondents were conducted using a structured questionnaire consisting of five-point Likert Scale statements which were designed to measure the attitude of the respondents. Data was analyzed using descriptive analysis, chi-square analysis, correlation analysis, factor analysis,and multiple regression. The descriptive analysis was undertaken to picture the characteristics of the respondents. The correlation analysis was used to describe the strength and direction of the linear relationship between socio-demographic profiles (age, gender, race, level of education, farming status, years of farming, income, quantity produced and farm size) and buyer-supplier relationship duration. Factor analysis was carried out to identify factors that influenced long-term buyer-supplier relationship. Meanwhile, multiple regression was conducted to determine the factors that mostly influenced long-term relationship between buyers and growers in the Malaysian pineapple industry. Finally, chi-square analysis was carried out to identify the benefits of long-term buyer-supplier relationships in the Malaysian pineapple industry in terms of years dealing with the existing buyers and growers and benefits obtained by these players. The findings based on the correlation analysis indicated that the growers’ age, years of farming, income, quantity produced, and farm size have positive relationships towards buyersupplier relationships except level of education, which showed a negative relationship towards the relationship. Meanwhile, from the buyers’ perspectives, age, years involved in business, income, and quantity purchased showed positive relationships towards the development of long-term buyer-supplier relationship. There was a similarity in accordance with growers’ findings that the level of education indicated a negative relationship. Briefly, the results of factor analysis and multiple regression revealed that in the Malaysian pineapple industry’s supply chain; from the growers’ perspectives, trust, power/dependence,loyalty and satisfaction were determined as the most influential determinants in maintaining long-term buyer-supplier relationships. Meanwhile, from the buyers’ perspectives, quality, satisfaction, and reputation were the most important factors in the development of long-term relationship. Finally, the chi-square analysis findings proved that due to the long-term relationship, both the growers and buyers perceived benefits as high profits, efficient distribution system, cost reduction, and increase quality. Generally, the results obtained from this study showed that the non-contract growers and buyers in the Malaysian pineapple industry have established the long-term relationships. As a conclusion, the results obtained from the analyses such as factor analysis, multiple regression and chi-square analysis proved that the concept of long-term buyer-supplier relationship among the Malaysian pineapple industry supply chain players particularly the growers and buyers played an important role in offering mutual benefits to both players.Potentially this may reflect the fact that majority of the pineapple growers and buyers in Malaysia are not bonded with a contractual agreement. The results from this study could provide an opportunity for the MPIB to establish effective strategies for production and marketing systems of small scale growers and buyers in the pineapple industry in Malaysia.